EVALUASI KINERJA DIVERSITAS ANTENA DARI SINYAL YANG SALING BERKORELASI - Alifiawan, Adis
Multipath fading is a phenomenon in wireless communication that has become the main cause for the quality decreasing of information transfer. One method that is usually used to overcome this problem is diversity. The type of diversity commonly been used is spatial diversity. Spatial diversity employ more than one antennas at the receiver which are separated with a particular distance among them. This final project will compare the performance of three diversity combining techniques. Those are Selection Combining (SC), Maximal Ratio Combining (MRC), and Equal Gain Combining (EGC). They will be tested using various correlated inputs. The research will be a computer simulation using MATLAB. The simulation includes transmitting, receiving, and error checking of the data. The performance parameters that will be considered are Bit Error Rate (BER) and Signal to Noise Ratio (SNR) of the combined signal. The result is if the correlation value becomes smaller, then the performance would be better. It is showed by the BER curves which are getting closer to the theoritical independent diversity performance curves. However, the improvement will be different between those three combining techniques. Simulations show that MRC is the best techniques because it produces the lowest BER compare to SC and EGC for the same input SNR. MRC is also the technique which produce the highest SNR of the combined signal.